2015
DOI: 10.1016/j.phytochem.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Interplays between the cell wall and phytohormones in interaction between plants and necrotrophic pathogens

Abstract: The plant cell wall surrounds every cell in plants. During microbial infection, the cell wall provides a dynamic interface for interaction with necrotrophic phytopathogens as a rich source of carbohydrates for the growth of pathogens, as a physical barrier restricting the progression of the pathogens, and as an integrity sensory system that can activate intracellular signaling cascades and ultimately lead to a multitude of inducible host defense responses. Studies over the last decade have provided evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 138 publications
3
48
0
5
Order By: Relevance
“…ABA can promote resistance against bacteria through its ability to induce stomata closure, blocking pathogen entry. On the other hand, ABA may promote pathogen virulence, since increasing ABA signaling or exogenous hormone application of ABA induces Pseudomonas syringe proliferation [47]. According to this observation, upregulation of ABA-related genes at early stage in CLas-infected Mexican lime plants could be related to pathogen modulation of host response in order to initiate plant colonization.…”
Section: Discussionmentioning
confidence: 94%
“…ABA can promote resistance against bacteria through its ability to induce stomata closure, blocking pathogen entry. On the other hand, ABA may promote pathogen virulence, since increasing ABA signaling or exogenous hormone application of ABA induces Pseudomonas syringe proliferation [47]. According to this observation, upregulation of ABA-related genes at early stage in CLas-infected Mexican lime plants could be related to pathogen modulation of host response in order to initiate plant colonization.…”
Section: Discussionmentioning
confidence: 94%
“…It was initially thought that these disease resistance phenotypes associated with alterations to cell wall integrity (CWI) were due to the inability of mis-adapted pathogens to overcome the genetically modified wall compositions/ structures in the plant mutants or over-expressor lines. However, this view was an oversimplification of the disease resistance phenotypes of these plant genotypes since it considered the wall to be just a passive barrier, whereas it has been found that activation of defensive signalling pathways does take place in mutants/transgenic plants with wall alterations (Miedes et al, 2014;Nafisi et al, 2015;Houston et al, 2016). In this section, we describe examples of the impact on disease resistance phenotypes of modifications of the main plant cell wall components, with a particular focus on published data for Arabidopsis genotypes (mutants and over-expressor lines) with altered wall composition (Table 1, Figure 1).…”
Section: Alterations To Plant Cell Wall Integrity Affect Disease Resimentioning
confidence: 99%
“…Some of these plants/mutants show altered disease resistance phenotypes that were initially associated with the mis-adaptation of pathogens to overcome the modified wall structures of these genotypes (5,7,(22)(23)(24)(25)(26)(27). However, activation of defensive pathways take place in the majority of these mutants/overexpressing lines with wall alterations (5,7,(22)(23)(24)(25)(26)(27). For instance, impairment of cellulose synthesis by inactivating cellulose synthase subunits, as it occurs in Arabidopsis thaliana irregular xylem mutants (irx1, irx3 and irx5), or for primary cell walls, as it takes place in Arabidopsis isoxaben resistant (ixr1)/constitutive expression of VSP (cev1) mutant, results in constitutive activation of some canonical defensive responses and enhanced resistance to different pathogens.…”
Section: Introductionmentioning
confidence: 99%